Semiotic Landscape in Cyprus: Verbo-Cultural Palimpsests as Visual Communication Strategy in Private (Shop) Signs in Limassol. - Papadima, Aspasia; Kourdis, Evangelos (My University, 2018)
The scope of this article is the semiotic study of the verbal, visual and spatial discourses as they are depicted on commercial signs in the city of Limassol, Cyprus that use modified verbal signs and verbo-cultural palimpsests for the purpose of commercial communication. It is widely believed that the marketplace of every city constitutes an aggregation of signs that form the image of the city. The contribution of this study lies in the fact that it focuses on the verbo-cultural palimpsests used on private signs, a special type of communication that scholars who study commercial communication have not yet paid much attention to.
Keywords: Graphic Design; Nonverbal Communication; Private Signs; Semiotic Landscape; Typography; Urban Semiotics; Verbo-Cultural Palimpsests